Ferroelectric Metal–Organic Framework as a Host Material for Sulfur to Alleviate the Shuttle Effect of Lithium–Sulfur Battery. Issue 61 (18th October 2020) - Zhu, Fulong; Tao, Yanli; Bao, Hongfei; Wu, Xuesong; Qin, Chao; Wang, Xinlong; Su, Zhongmin
Abstract: Ferroelectricity has an excellent reversible polarization conversion behavior under an external electric field. Herein, we propose an interesting strategy to alleviate the shuttle effect of lithium–sulfur battery by utilizing ferroelectric metal–organic framework (FMOF) as a host material for the first time. Compared to other MOF with same structure but without ferroelectricity and commercial carbon black, the cathode based on FMOF exhibits a low capacity decay and high cycling stability. These results demonstrate that the polarization switching behaviors of FMOF under the discharge voltage of lithium–sulfur battery can effectively trap polysulfides by polar–polar interactions, decrease polysulfides shuttle and improve the electrochemical performance of lithium–sulfur battery. Abstract : Ferroelectric effect produced by polarization conversion of ferroelectric metal–organic framework is used to inhibit polysulfides shuttle and improve the electrochemistry of lithium–sulfur battery.